THE ROLE OF NEUROMARKETING IN DECODING BRAIN STIMULI AND CONSUMER BEHAVIOR (International Journal of Management Trends: Key Concepts and Research, 2024)
This study focuses on the field of neuromarketing and its relationship with consumer behaviour. In a context where advances in neuroimaging and technology have allowed a detailed study of neuronal activity, neuromarketing emerges as a discipline that fuses brain science with marketing strategies. This new approach has revolutionized the understanding of sensory stimuli by interconnecting the five senses, emotions and consumer decisions. The research focuses on the application of neuromarketing techniques that help to understand how certain marketing stimuli can influence consumer behaviour and their purchasing deci-sion-making process. In addition, the concept of "applied organizational neuroscience" is addressed, highlighting a paradigm shift in the traditional marketing approach towards a deeper insight of the consumer mental processes. Through an analytical and documentary research, this study analyses the fundamental principles of neuromarketing, sensory marketing and consumer behaviour. It explores how brain processes influence consumer perception, decision-making, and emotional responses to de-velop the most effective marketing strategies. By a better understanding of those processes, this study provides key elements to stand out in an increasingly competitive and demanding market. The objective is to investigate the influence of neuromarketing on consumer purchasing decisions and to explore consumers' attitudes towards neuromarketing and its impact on purchasing decisions.